1982
DOI: 10.1029/wr018i005p01365
|View full text |Cite
|
Sign up to set email alerts
|

Use of atmospheric fluorocarbons F‐11 and F‐12 to determine the diffusion parameters of the unsaturated zone in the Southern High Plains of Texas

Abstract: Two stable, entirely man-made fluorocarbon gases, trichlorofluoromethane (F-11) and dichlorodifluoromethane (F-12), have been released into the atmosphere during the past 40 years as a consequence of their widespread commercial use. Production data for these compounds are well documented, and atmospheric buildup can be reconstructed on the basis of published release estimates. On-site measurements of F-I 1 and F-12 concentrations in soil air within unconsolidated sedimentary deposits were made using gas chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 29 publications
2
79
0
Order By: Relevance
“…The migration of a reactive gas moving through a variably saturated media has been investigated (Weeks, Earp and Thompson 1982;Kreamer, Weeks, and Thompson 1988;Gierke, Hutzler, and Crittenden 1990). Partitioning between the gas phase and the aqueous phase and between the aqueous phase and solid phases retards the diffusion of the reactive gas.…”
Section: Substituting Equation 8 Back Into Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…The migration of a reactive gas moving through a variably saturated media has been investigated (Weeks, Earp and Thompson 1982;Kreamer, Weeks, and Thompson 1988;Gierke, Hutzler, and Crittenden 1990). Partitioning between the gas phase and the aqueous phase and between the aqueous phase and solid phases retards the diffusion of the reactive gas.…”
Section: Substituting Equation 8 Back Into Equationmentioning
confidence: 99%
“…Many relations between porosity and gas-phase diffusion have been suggested and tested (Millington 1959;Currie 1960a;Currie 1960b;Weeks, Earp, and Thompson 1982;Sallam, Jury, and Letey 1984;Kreamer, Weeks, and Thompson 1988;Lerman 1988). Particle shape and particle size distribution affect gas diffusion and how diffusion changes with moisture content.…”
Section: Diffusionmentioning
confidence: 99%
“…In deeper unsaturated zones of simple porous aquifers, there is a lag time for the diffusive transport of both CFCs and SF 6 through the unsaturated zone. The time lag is a function of the tracer diffusion coefficients, tracer solubility in water, and soil water content (Weeks et al, 1982;Cook and Solomon, 1995). In a deep unsaturated zone the apparent tracer age will be older than the true age of recharge.…”
Section: Unsaturated Zone Processesmentioning
confidence: 99%
“…b from Weeks et al 1982 c from Moldrup et al 1997;and included in Moldrup et al 2000a (undisturbed soils) d from Moldrup et al 1997;and included in Moldrup et al 2000b (re-packed soils) e modified from Moldrup et al 1997;reported in Costanza-Robinson and Brusseau 2002 interval directly from the cylinder (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Several methods exist for measuring or estimating tortuosities for unsaturated porous-media systems, including laboratory methods, empirical relationships, and field methods (e.g., Lai et al 1976;Weeks et al 1982;Reid et al 1987;Moldrup et al 1997Moldrup et al , 2000a. In-situ measurement of physical properties is generally considered to provide more representative results than laboratory-measured values for field-scale applications.…”
Section: Introductionmentioning
confidence: 99%